2002
DOI: 10.1258/0956462021925063
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial co-infection among patients with gonorrhoea

Abstract: The objective was to determine how often gonococcal (GC) infection is accompanied by chlamydial co-infection and to determine risk factors for dual infection. All GC-positive cultures were identified between 24 April and 9 September 1998, among patients seen at the three genitourinary medicine (GUM) clinics across the Chelsea and Westminster Directorate. Chlamydia trachomatis was diagnosed using an enzyme-linked immunosorbent assay (ELISA) (Dade-Behring). One hundred and fifty-three episodes of gonorrhoea were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
4
19
1
Order By: Relevance
“…Our data indicate that proportions of either gonorrhoea co-infection with chlamydia or chlamydia co-infection with gonorrhoea are substantially high (65%, 95% CI 56-71%) among FSWs in the study area, which supports the recommendation in the national STD guidelines that patients infected with gonorrhoeae also be treated routinely with anti-chlamydial regimen. 8 In common with the findings from other studies, 9,13 co-infection become less common with increasing age in our study. Age younger than 20 years has been considered as one of factors to offer empirical anti-chlamydial treatment for patients with gonorrhoea.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data indicate that proportions of either gonorrhoea co-infection with chlamydia or chlamydia co-infection with gonorrhoea are substantially high (65%, 95% CI 56-71%) among FSWs in the study area, which supports the recommendation in the national STD guidelines that patients infected with gonorrhoeae also be treated routinely with anti-chlamydial regimen. 8 In common with the findings from other studies, 9,13 co-infection become less common with increasing age in our study. Age younger than 20 years has been considered as one of factors to offer empirical anti-chlamydial treatment for patients with gonorrhoea.…”
Section: Discussionsupporting
confidence: 92%
“…Age younger than 20 years has been considered as one of factors to offer empirical anti-chlamydial treatment for patients with gonorrhoea. 9 However, our results indicated that if the empirical anti-chlamydial treatments were only provided to those with gonorrhoea who are younger than 20 years, the sensitivity, specificity, PPV and NPV of this treatment strategy would be much low for chlamydial treatment (31%, 53%, 49% and 35%, respectively). Increase of sensitivity through providing treatment to all patients with gonorrhoea and those aged younger than 20 years has significantly decreased the specificity from 68% to 11%.…”
Section: Discussionmentioning
confidence: 64%
“…This is lower than has been reported in other studies, however, a rate of 10.7% has recently been reported in another London genitourinary medicine (GUM) clinic 19 .…”
Section: (3) All Patients With Gonorrhoea Should Be Screened For Genicontrasting
confidence: 65%
“…More recently, Ginocchio et al showed that among women in the USA the prevalence of dual infections was five times higher in African-American women aged 18–89 years than Caucasians: CT/TV (3.6% vs 0.6%), CT/NG (1.7% vs 0.4%), TV/NG (1.7% vs 0.5%), but no data were available on age-specific relationships, nor in men 20. High prevalence of CT and NG coinfections (but no corresponding TV data) have been reported in the UK among people of black Caribbean ethnic origin21 and in the Netherlands among people of Surinam or Antillean origin 22. In many of these settings, the higher prevalences of STIs and coinfections in ethnic minority groups are believed to be due to inequities in access to healthcare 23 24…”
Section: Discussionmentioning
confidence: 97%